Kontribusi Guru Dalam Pelaksanaan ANBK Untuk Meningkatkan Dan Mengimplementasikan Program AKM Literasi Dan Numerasi Siswa - Muhammad Hanif; Alfiana Shinta Putri; Nesya Priyandia; Ghefira Syahrani Putri; Andrian Manogu; Maghfiroh Wachidah Rohmah (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
Minimum Competency Assessment (AKM) is a measure of literacy and numeracy achievement that is used to map the quality of education in Indonesia with international standards. How important is AKM training because it increases teacher competence to develop a learning framework that leads to student reasoning in literacy and numeracy and character surveys. The purpose of this analysis is to ensure that the AKM training for teachers greatly impacts the development of the learning framework and motivates teachers to participate in the training enthusiastically and apply it consistently to students. This analysis uses a literature review method taken from various reading sources and the analysis that has been carried out. The findings in this study are teachers still use a standard learning framework by providing an assessment that is limited to testing memory. The results of this study are recommendations for teachers to be enthusiastic about developing competencies and become study material for further research.